PHYTOCHEMICALS SCREENING AND ANTIOXIDANT ACTIVITY TEST OF ETHYL ACETATE FRACTION OF CHINESE BETLE LEAVES (Peperomia pellucida L.) - Naida Rahma Almira; Didin Ahidin; Iin Indawati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Peperomia pellucida (Chinese betel) is considered as a plant with antioxidant activity forÂ inhibiting oxidation reactions. This study aims to determine the yield of secondary metabolites, total flavonoid levels, and antioxidant activity. Dried leaves of Chinese betel were macerated using 70% ethanol as solvent. The extract was partitioned until the n-hexane and ethyl acetate fractions were obtained. A phytochemical screening test was followed by determining total flavonoid levels and antioxidant activity using UV-Vis spectrophotometry. Phytochemical screening results containing an ethanolic extract of Chinese betel leaves (ECBL) showed positive results on alkaloid, flavonoid, saponin, and tannin. Meanwhile, the ethyl acetate (EAF) and n-hexane (HF) fractions showed positive results only for flavonoid presence. The total flavonoid contents of ECBL, EAF, and HF were 3.30%, 2.54%, and 2.03%, respectively. The IC50 values of Â ECBL, EAF, and HF were 7.51 ppm, 8.02 ppm, and 8.04 ppm, respectively. The highest flavonoid content was found in ECBL. Antioxidant activity test of Peperomia pellucida ethanolic extract, ethyl acetate fraction, and n-hexane fraction showed potent antioxidant activity. Â Keywords: Antioxidant, Peperomia pellucida , DPPH